ANALISIS KEBIJAKAN PAJAK PERDAGANGAN MELALUI SISTEM ELEKTRONIK DI INDONESIA PADA ERA PANDEMI - Afian Dezi Sanda Sipi (Gapenas Publisher, 2022)
The purpose of this study is to determine the implementation of trade taxes through an electronic system that has been implemented in Indonesia during the pandemic. This study uses a qualitative descriptive research method using SWOT (strength, weakness, opportunity, threats) analysis to determine the strengths, weaknesses, opportunities, and threats of the Digital Tax/PMSE policy in Indonesia. The results of this study indicate that the potential of Digital Tax/PMSE policies in Indonesia can be carried out to the maximum by still paying attention to and minimizing the threats and weaknesses that occur so that digital taxes in Indonesia can succeed fairly and state income can increase in the pandemic era. The issuance of the PMK 48/03/2020 is a solution to optimize tax revenues to increase